Does pelvic floor muscle contraction early after delivery cause perineal pain in postpartum women?. (January 2017) - Neels, Hedwig; De Wachter, Stefan; Wyndaele, Jean-Jacques; Wyndaele, Michel; Vermandel, Alexandra
Abstract: Objective: Pelvic floor muscle training is effective and necessary in the prevention and treatment of pelvic floor dysfunction during pregnancy and after childbirth. But because of the high prevalence of perineal pain observed in women after childbirth, many women and caregivers fear to start pelvic floor muscle training immediately after childbirth. However, it is unknown whether pelvic floor muscle contractions (PFMC) provoke perineal pain in women shortly after childbirth. Therefore, the main objective is to study whether PFMC performed immediately after childbirth is painful or not. Study design: Observational longitudinal study. Perineal pain was assessed (1–6 days and 9 weeks postpartum) using a visual analogue scale (VAS 0–10) during PFMC and during several activities of daily living (ADL), during micturition and defecation. Descriptive statistics, Wilcoxon and McNemar tests were used. Results: A total of 233 women participated (148 primiparous and 85 multiparous). Immediately postpartum the prevalence and intensity of pain during ADL (73%; VAS 4.9 (±2.3)), micturition (47%; VAS 3.4 (±1.7)) and defecation (19%; VAS 3.6 (±2.2)) were significantly higher (all p < 0.000) than during PFMC (8%; VAS 2.2 (±0.9)). At 9 weeks postpartum, 30% experienced perineal pain during sexual intercourse (VAS 4.6 +/− 2.3) and 18% during defecation (VAS 4.7 +/− 2.3), but none during PFMC. Conclusion: Perineal pain is highly prevalent immediately after childbirth during ADL, micturition and defecation, but not during PFMC (only 8%). In case perineal pain occurs during PFMC, the intensity of pain is low (VAS 2). These results show that fear of perineal pain should not discourage women to start pelvic floor muscle training shortly after childbirth.